COVID-19 Like Findings in a Fatal Case of Idiopathic Desquamative Interstitial Pneumonia Associated With IgA Glomerulonephritis in a 13-Month-Old Child - Gurzu, Simona; Satala, Catalin Bogdan; Melit, Lorena Elena; Streinu-Cercel, Adrian; Otelea, Dan; Capalna, Brandusa; Puiac, Claudiu Ioan; Szederjesi, Janos; Jung, Ioan (Frontiers in Pediatrics, 2020)
In the COVID-19 era, patients with severe acute respiratory syndrome (SARS) are suspected to be associated with SARS-CoV-2 infection. The aim of this paper is to present a case with COVID-like pneumonia, with fatal evolution. The clinical aspects were correlated with the autopsy findings and discussed on the background of the most recent data from the medical literature. A 13-month-old girl was admitted to the emergency room with acute severe shortness of breath and pulmonary bilateral ground-glass opacities and an almost complete opacified left lung. The patient suddenly deteriorated, and death was confirmed three hours after admission. At autopsy, severe desquamative interstitial pneumonia was diagnosed and was associated with an unusual IgA glomerulonephritis. No SARS-CoV-2 infection was detected in the lung parenchyma by RT- PCR. This is a very unusual case of rapid deterioration of an infant with idiopathic desquamative interstitial pneumonia (IDP) and multiorgan involvement. Based on immunohistochemical stains, we hypothesize that, in IDP, the hyaline membranes arise from necrotizing desquamated pneumocytes. In the COVID-19 era, such cases are extremely difficult to diagnose; they can mimic SARS-CoV-2-induced lung injuries. This pattern of hyaline membrane formation might explain the poor response to oxygen therapy. The present case highlights the importance of autopsy in such challenging cases.